2023
DOI: 10.3390/beverages9030059
|View full text |Cite
|
Sign up to set email alerts
|

Live, Probiotic, or Neither? Microbial Composition of Retail-Available Kombucha and “Hard” Kombucha in the Pacific Northwest of the United States

Keisha Harrison,
Roxana Navarro,
Kristen Jensen
et al.

Abstract: Kombucha is an acidic non-alcoholic fermented tea beverage that has surged in popularity over the past decade. A key driver of this popularity is the perception that kombucha contains microbes that contribute to gut health, a perception that is reinforced by package claims such as “live” and “probiotic”. We surveyed retail-available non-alcoholic (soft) and alcoholic (hard) kombucha and selected 39 products, of which 74.4% included at least one of these claims. Based upon Nuclear Magnetic Resonance (NMR) evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Recently, six different retail Kombuchas in New Zealand were analyzed and found only three contained viable cultures [11]. Studies have reported on inconsistencies in product labels of retail Kombucha drinks regarding the term 'probiotic' and actual viable cultures present, indicating a growing need to further standardize labeling to reflect the probiotic potential of available Kombucha products more accurately [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, six different retail Kombuchas in New Zealand were analyzed and found only three contained viable cultures [11]. Studies have reported on inconsistencies in product labels of retail Kombucha drinks regarding the term 'probiotic' and actual viable cultures present, indicating a growing need to further standardize labeling to reflect the probiotic potential of available Kombucha products more accurately [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, six different retail Kombuchas in New Zealand were analyzed, and it was found that only three contained viable cultures [ 11 ]. Studies have reported inconsistencies in product labels of retail Kombucha drinks regarding the term ‘probiotic’ and actual viable cultures present, indicating a growing need to further standardize labeling to reflect the probiotic potential of available Kombucha products more accurately [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include genera of AAB ( Komagataeibacter , Gluconobacter , and Acetobacter ) [ 14 ], LAB ( Lactobacillus , Oenococcus , and Lactococcus ) [ 10 ], and yeasts ( Saccharomyces , Zygosaccharomyces , Torulaspora , and Brettanomyces ) [ 9 ]. Defined probiotic cultures are sometimes added in commercial Kombuchas to potentially enhance the nutraceutical aspect of the beverage [ 12 ].…”
Section: Introductionmentioning
confidence: 99%